Myocardial ischemia-reperfusion injury and melatonin - Şahna, Engin; Deniz, Esra; Aksulu, Hakki Engin (My University, 2006)
It is believed that myocardial ischemia-reperfusion injury is related to increased free radical generated and intracellular calcium overload especially during the period of reperfusion. The pineal secretory product, melatonin, is known to be a potent free radical scavenger, antioxidant and can inhibit the intracellular calcium overload. In this review, we have summarized the fundamental of cardiac ischemia-reperfusion injury and the effects of melatonin on myocardial damage that related to cardiac ischemia-reperfusion injury. The total antioxidant capacity of human serum is related to melatonin levels. Incidence of sudden cardiac death is high in the morning hours. It has been shown that melatonin levels are significantly low at these times and patients with coronary heart disease have lower than normal individuals. These findings thought that melatonin would be valuable to test in clinical trials for prevention of possible ischemia-reperfusion-induced injury, especially life threatening arrhythmias and infarct size, effecting life quality, associated with thrombolysis, angioplasty, coronary artery spasm or coronary bypass surgery.
Miyokardiyal iskemi-reperfüzyon hasari ve melatonin
Keywords: Ischemia; Melatonin; Reperfusion